Integration of the Webqual 4.0 and UEQ Methods in Evaluating the Impact of the Student Recruitment Information System on Business Efficiency and Admissions Services (Case Study: Sari Mutiara Indonesia University) - Lius Luaha; Delisman Hulu; Rianto Sitanggang (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This study aims to evaluate the service quality of the New Student Admission Information System (PMB) at Sari Mutiara Indonesia University and its impact on business efficiency using the WebQual 4.0 method and the User Experience Questionnaire (UEQ). Based on a population of 1,700 users, the sample size was determined using the Slovin formula (5% margin of error), resulting in 324 respondents (319 prospective students, 5 admissions staff) selected via purposive sampling. The WebQual 4.0 evaluation yielded an average score of 4.05 (Good category), with the Usability dimension scoring highest (4.30) and Service Interaction lowest (3.80). UEQ analysis showed that all scales fell within the positive category (>0.8), with the main strength lying in the pragmatic aspect of Perspicuity (2.36), whilst recording the lowest score in the hedonic aspect of Novelty (1.47). Operationally, the system’s high ease of use has been shown to reduce data verification time by 75% (from 20 to 5 minutes) and lower the human error rate from 12% to below 2%. In conclusion, the PMB system operates very efficiently from a business perspective and is user-friendly; however, an update to the user interface (UI/UX) is urgently needed to enhance the novelty value, along with the integration of a more responsive technical support service.